Primary Malignant Mucosal Melanoma of the Esophagus. A Case Report - Lequaglie, Cosimo (2023)
Primary malignant melanoma isa rare lesion, that accounts for only 0.1 % of primary esophageal malignant neoplasms. The tumor is polypoid, pedunculated and sometimes ulcerated. Symptoms are similar to those of squamous cell carcinoma and the preoperative differential diagnosis is important. Surgical resection is the treatment of choice. In tracavitary radiotherapy may be a useful form of adjuvant therapy in selected patients. Here we record the case of a 67 years old man with a primary malignant melanama of the esophagus. He underwent an esophagectomy, and is stili alive 5 months aftnr lhe procedure.